Public Service Innovation on Stunting Overcoming in North Luwu Regency - Idrus, Iqbal Aidar; Syah, Syahiruddin (Universitas Padjadjaran, 2024)
The dispute of stunting tends to be a severe public health problem in Indonesia, including in North Luwu Regency. Stunting has a long-term impact on children's physical growth, cognitive development, and health. Furthermore, it has the potential to cause lasting health and social problems. Therefore, this research proposes to explore and evaluate public service innovations that have helped overcome stunting in North Luwu Regency. This research implies a qualitative method with a documentation approach and data analysis using Nvivo 12 Plus software, as well as validation through data triangulation from various sources to ensure the accuracy and trustworthiness of the findings. The findings of this study show that North Luwu Regency, through the